Optimization Of Village Natural Resource Management Policies by Village-Owned Enterprises (BUMDES) to Improve Local Community Welfare - Apolo Justino França da Silva; Pudji Astuty (PT. ALHAFI BERKAH INDONESIA, 2025)
The management of natural resources (NR) in villages has great potential to support the improvement of local community welfare, yet in reality, many villages have not been able to systematically and sustainably optimize their natural wealth. Village-Owned Enterprises (BUMDes), as economic and legal entities mandated by Law Number 6 of 2014 concerning Villages, hold a strategic position to manage these potentials. This study aims to analyze the role and optimization of village NR management policies through BUMDes as a means to create community welfare, as well as to examine obstacles encountered in practice. Using a normative juridical approach and analysis of the latest regulations such as Government Regulation No. 11 of 2021, Law No. 23 of 2014, Law No. 6 of 2023, and Law No. 32 of 2009, this research highlights the importance of regulatory synchronization and strengthening the institutional capacity of BUMDes. The findings indicate that although there is a sufficiently strong legal basis, many BUMDes lack legal entity status, experience managerial limitations, and have minimal technical regulatory support at the regional level. Therefore, policy optimization through the formulation of Village Regulations, harmonization with regional development planning, and enhancement of human resource competencies is essential. Institutional strengthening and cross-sectoral support are considered capable of expanding positive impacts such as increasing original village revenue, creating employment, and empowering vulnerable groups. This study recommends sustained collaboration among government, community, and private sectors as a pathway toward village welfare based on local independence.